French validation of the Emotion Regulation Skills Questionnaire Validation française du Questionnaire de Compétences en matière de Régulation Émotionnelle - Nardelli, Carla; Montreuil, Tina; Naoufal, Michael; Berking, Matthias; Baeyens, Céline; Bortolon, Catherine (European Review of Applied Psychology-Revue Europeenne De Psychologie Appliquee, 2024)
Background: Emotion regulation (ER) has become the target of multiple clinical interventions, given its transdiagnostic features. The goal of this study was to validate a French version of the Emotion Regulation Skills Questionnaire (ERSQ, Berking & Znoj, 2008), which provides an overview of the ER skills described in the Adaptive Coping with Emotions model. Method: This online study was comprised of different questionnaires designed to analyse the psychometric properties of the ERSQ in both French and Canadian non-clinical populations (n = 658). Results: The nine subscales based on the nine factors show a satisfactory internal consistency. The scale also demonstrates good convergent validity and acceptable test-retest validity. The proposed nine-factor model shows an adequate fit to the data, with all approximate fit indices showing acceptable model fit. Limitation: This online study can be associated with common limits of self-reported measures. Moreover, our results should be replicated in future studies, for example in clinical samples, to validate its discriminant capacity. Conclusions: The French version of the ERSQ can be considered as a reliable instrument for assessing ER skills. Contrary to other related questionnaires, the ERSQ measures multiple dimensions considered as possible targets of psychological interventions.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Assessment; Emotion regulation; Emotion regulation skills; Reliability; Validity